Keefektifan Ujian Berbasis Komputer Menggunakan Aplikasi CANDY CBT di SMA Muhammadiyah Maumere - Atanggae, Dian Syahria; Angelaus Ete, Agustinus; Dhema, Magdalena (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2024)
This study aims to determine the effectiveness of computer-based exams using the Candy CBT application at SMA Muhammadiyah Maumere. The population of this study were students of class XI, totaling 63 students. The sample in the study consisted of 45 students. Data collection techniques using questionnaires or questionnaires. This research uses a quantitative approach and uses a descriptive analysis method. After the questionnaire is said to be valid and reliable, it is followed by a descriptive analysis of the results of the respondents' scores and a descriptive analysis of the average percentage of each indicator. Based on the calculation results obtained data on the results of the questionnaire score in each statement item as many as 29 students answered with a score of 68% - 83% included in the "high" criteria. In addition, based on descriptive analysis of each indicator related to the user's satisfaction in this study, the criteria for "high” ranges were obtained. Based on the calculation data it can be seen that the average percentage of effective examination of computer-based exams using the Candy CBT application is 77.5% and is in the effective category. So that it can be concluded that the use of the Candy CBT application during computer-based exams is very effectively applied at SMA Muhammadiyah Maumere seen from the overall response of students to user satisfaction.